General Studies in the University Curriculum. An Analysis of its Relevance - Chayña Aguilar, Luis; Álvaro Fernández, Delcy Gladys; Cruz Cervantes, Jesús Manuel; Carrasco Reyes, Percy Rogelio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
A study is presented whose purpose is to analyze the belonging, tendency and challenges of general studies in curricula of academic programs of Peruvian Universities. The study, carried out according to the phenomenological design, was made up of university teachers familiar with the curriculum chosen until saturation was achieved. A questionnaire of open questions was applied focused on the appreciation of the informants in the object of the investigation and as results it was found that the general studies contribute: to the development of soft skills in the integral formation of the student, to the identification of strengths and interests about the profession, to the civic life, to the discovery and the reaffirmation of the vocation; hence its curricular relevance.